2021
DOI: 10.1155/2021/1704947
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Relationships among Children’s Perceived Competence, Motor Skill Competence, Physical Activity, and Cardiorespiratory Fitness across One School Year

Abstract: Purpose. The bidirectional associations among children’s motor skill competence (MSC), perceived competence (PC), physical activity (PA), and cardiorespiratory fitness (CRF) over time remain unanswered. This study is aimed at discerning the bidirectional relationships among elementary school children’s MSC, PC, PA and, CRF over the course of one school year. Methods. A total of 261 second and third grade children (127 boys, 134 girls; mea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 72 publications
1
8
0
Order By: Relevance
“…Furthermore, our total sample data indicated no significant bidirectional or predictive relationship between MSC and PC, indicating that MSC and PC were not considered as significant contributors of each variable. These observations aligned with a recent study that was held in two U.S. elementary schools [ 43 ]. However, several previous studies showed inconsistent findings [ 21 , 22 , 59 , 60 ].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Furthermore, our total sample data indicated no significant bidirectional or predictive relationship between MSC and PC, indicating that MSC and PC were not considered as significant contributors of each variable. These observations aligned with a recent study that was held in two U.S. elementary schools [ 43 ]. However, several previous studies showed inconsistent findings [ 21 , 22 , 59 , 60 ].…”
Section: Discussionsupporting
confidence: 90%
“…Our study has several strengths. First, our study used a cross-lagged panel model approach, which allows us to investigate the direction and strength of the associations between PA, MSC, and PC by testing bidirectional relationships between the variables [ 43 ]. Second, we used objective measurements to assess PA, MSC, and PC in preschool children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Without a certain physical fitness level and basic competencies in different motor skills, children are limited in the amount and range of PA they can undertake [ 8 ]. According to the literature, there is a strong association between motor skill performance, physical fitness, and PA participation [ 9 , 10 ]. Therefore, strategies aiming to improve children’s PA need to ensure children have the competency to be physically active in the first place [ 11 ].…”
Section: Introductionmentioning
confidence: 99%